Use of Information Sources by Faculty Members of Allopathy and Ayurveda Colleges in Kerala: A Comparative Analysis - Prakasan, P. M. (Journal of Information and Knowledge, 2020)
This paper examines the use of Internet and information resources by the faculty members of government medical colleges in Kerala and makes a comparative analysis of Allopathy and Ayurveda college teachers. Stratified sampling method was used to select the sample of 273 faculty members of Allopathy colleges and 123 faculty members from Ayurveda colleges. A questionnaire was the instrument for data collection. The analysis reveals that there exist significant differences between Allopathy and Ayurveda college faculty members in terms of the purpose of using Internet. There are differences between Allopathy and Ayurevda faculty members of Kerala. A few suggestions have been made to enhance the quality and quantity of information resources and services in these colleges.